Field Archaeology from Around the World : Ideas and Approaches - Carver, Martin; Gaydarska, Bisserka; Montón-Subías, Sandra (SpringerBriefs in Archaeology, 2015)
Field practice in archaeology varies greatly throughout the world, mainly because archaeological sites survive in very different ways in different counties.  Many manuals see this as a problem - to be defeated by the imposition of standardised procedures.  In this book we relish the variety of field practice, seeing it rather as the way the best archaeologists have responded creatively to the challenges of terrain, research objectives and the communities within which they work.  While insisting on the highest levels of investigation, we celebrate the different designs, concepts, scientific detection methods and recording systems applied - so embracing standards, but not standardisation. The book is organised in four parts:  Part 1 offers a summary of field procedures. Part 2 reviews the principal methods applied, above and below ground, and how the results are analysed. Part 3 illustrates the huge variety confronted by field workers with a series of exemplary commercial and academic projects enacted in downland, jungle, desert, permafrost, road schemes and towns.  Approaches also differ according to the traditional methodologies that have evolved in particular countries.  In Part 4 we give examples of some the strongest and oldest of those practised on four continents.